The stock market and the ringgit exchange rate: A note - Baharumshah, Ahmad Zubaidi; M. Masih, A.Mansur; Azali, M (2002)
This paper presents and tests an augmented monetary model that includes the effect of stock prices on the bilateral exchange rates. The model is applied to the ringgit/US dollar (RM/US) ang ringgit/Japanese yen (RM/JY) exchange rates. The empirical analysis is conducted by the Johansen method of cointegration. Using the data from the recent float that ends with 1996:Q4, the study is motivated, among others, by an interesting preliminary finding that although the augmented monetary model is cointegrated, it is subject to parameter instability and that the parameter time dependency can be attributed at least partly to aparticular subset of the variables in the system including stock prices. We find that a restricted VAR model which imposes exogeneity restrictions on I(1) variables, such as stock prices, among others, exhibits both cointegration and parameter stability. In addition, we demonstrate that exchange rate adjusts to clear any disequilibrium in the long-run relationship. The empirical findings tend to suggest that the equity market is significant in affecting the exchange rate and in explaining at least in part the parameter instability evidenced in the cointegrating system. Hence, we conclude that models of equilibrium exchange rate should be extended to include equity markets in addition to bond markets. © 2002 Elsevier Science B.V. All rights reserved.